2013
DOI: 10.1002/adfm.201303401
|View full text |Cite
|
Sign up to set email alerts
|

We Want Our Photons Back: Simple Nanostructures for White Organic Light‐Emitting Diode Outcoupling

Abstract: Conventional planar organic light-emitting diodes (OLEDs) suffer from poor light extraction due to the total internal refl ection at the waveguided interfaces. Therefore, the development of effi cient light extraction structures is of great necessity and signifi cance to realize practical applications in large area and cost-effective light sources. In this paper, a high-performance internal light outcoupling system for white OLEDs with spontaneously formed metal oxide nanostructures is developed. The fabricati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…Recently, the electrical conductivity of PEDOT:PSS films was increased to 4380 S/cm through H 2 SO 4 post-treatment [18]. Many research groups have reported flexible OLEDs in which PEDOT:PSS thin films are used as TCEs [19][20][21][22][23][24]. The insufficient electrical conductivity of PEDOT:PSS is an impediment to its use as a TCE in an OLED.…”
Section: Conducting Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the electrical conductivity of PEDOT:PSS films was increased to 4380 S/cm through H 2 SO 4 post-treatment [18]. Many research groups have reported flexible OLEDs in which PEDOT:PSS thin films are used as TCEs [19][20][21][22][23][24]. The insufficient electrical conductivity of PEDOT:PSS is an impediment to its use as a TCE in an OLED.…”
Section: Conducting Polymermentioning
confidence: 99%
“…To separate the PEDOT and PSS domains, several types of polar solvent additives have been used [13,[25][26][27][28][29][30][31][32][33][34][35]. Methods of removing the PSS chains in PEDOT:PSS thin films have been reported and can effectively improve their electrical conductivity [18][19][20][21][22][23][24]. Several polar solvents that can be used to improve the electrical conductivity of PEDOT:PSS electrodes have been reported (Table 1) [13,[28][29][30][31][32][33][34][35].…”
Section: Conducting Polymermentioning
confidence: 99%
“…The internal method focuses on the extraction of the waveguided modes or the light guided along the electrode (e.g. ITO)/organics layers [16][17][18][19]. In order to achieve high light out coupling effects various approaches have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…In order to replace ITO, therefore, alterna-60 tive transparent and conductive electrodes including silver 61 nanowires [8,[12][13][14][15][16][17], carbon nanotubes [18,19], thin metal 62 films [20,21], graphene [6,7, [22][23][24][25], and conductive poly-63 mers [26][27][28] have been intensively investigated. In partic- [29][30][31][32][33][34][35][36]. 68 In fact, PEDOT:PSS is one of the well-known hole inject- 69 ing material in the OLEDs due to its high transmittance and 70 good electrical conductivity [37].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to flexibility 71 from the polymeric material property, PEDOT:PSS has an 72 advantage of a facile controllability of its conductivity. 73 Therefore, in order to use it as anode material, many 74 research groups have doped PEDOT:PSS with various 75 materials such as dimethyl sulfoxide (DMSO) [29] glycol (EG) [30,31], glycerol [32], and N,N-dimethylacet-77 amide (DMAc) [33]. Although such anodes have been 78 applied for OLEDs, their current and power efficiencies were 79 still low comparing with the device with ITO anodes [29-80 35].…”
Section: Introductionmentioning
confidence: 99%